Efecto de intervención educativa en la recuperación de desnutrición aguda en niños atendidos en Centro de Salud San Juan – 2008 - Correa Cajachagua, Maribel Toribia (2013)
The present research work entitled "Effect of educational intervention in the recovery of acute malnutrition in children treated at the San Juan Health Center - 2008", had the general objective: To determine the effect of a nutritional educational intervention program, in the recovery of children with acute malnutrition aged 1 to 3 years. The type of research that was used was the quasi-experimental, correlational-causal design in time series with a single group, the study was longitudinal, the information was collected by stages and steps throughout 4 months of the intervention. The sample size was 20 children from 1 to 3 years of age treated at the San Juan Health Center in the San Juan district. To collect the information, three instruments were used: Anthropometric evaluation form and auxiliary tests; Food and nutrition knowledge questionnaire (pre and post test) and Dietary practices report sheet. The Questionnaire had a validity of 77% and a reliability of Crombach's alpha = 0.6. The data collected were analyzed using the SPSS version 15 program. The hypothesis was verified using the t test for related samples and X2 for a sample with α = 0.05. Among the most relevant findings we can cite: The educational intervention program had a positive effect on the nutritional recovery of children with acute malnutrition, evidenced in the following: The knowledge and skills of the mother on issues of nutrition, malnutrition, anemia, parasitosis, food hygiene and common infections (acute diarrheal diseases and acute respiratory infections) are adequate due to the effect of the nutritional educational intervention program, according to t (19) = 25.90 , p = 0.00 ≤ than α = 0.05; the weight and height of the child, the subject of the study, reaches appropriate standards for the age at the end of the nutritional educational intervention, according to: t (19) = -7.172, p ≤ 0.000, α ≤ 0.05; for the weight t (19) = -0.2896, p ≤ 0.009, α ≤ 0.05; for size; the study children reached adequate hemoglobin levels as a positive effect of the nutritional educational intervention according to t (19) = -3706 p ≤ 0.001, α ≤ 0.05 and the educational intervention program had no effect on the control of parasitosis according to X2 (1) = 3,200, p = 0.074 ≤ α = 0.05.